Negative thermal expansion of fullerite C₆₀ at liquid helium temperatures - Aleksandrovskii, A.N.; Esel`son, V.B.; Manzhelii, V.G.; Soldatov, A.V.; Sundqvist, B. (Физика низких температур, 1997)
The thermal expansion of fullerite C₆₀ has been measured in the temperature range 2-9 К A compacted fullerite sample with a diameter of about 6 mm and height of 2.4 mm was used. It was found that at temperatures below - 3.4 К the linear thermal expansion coefficient becomes negath re. At temperatures above 5 К our results are in good agreement with the available literature data. A qualitative explanation of the results is proposed.